2007
DOI: 10.1007/s11433-007-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulated evolution process of core-shell microstructures

Abstract: The evolution process of core-shell microstructures formed in monotectic alloys under the space environment condition was investigated by the numerical simulation method. In order to account for the effect of surface segregation on phase separation, Model H was modified by introducing a surface free energy term into the total free energy of alloy droplet. Three Fe-Cu alloys were taken as simulated examples, which usually exhibit metastable phase separation in undercooled and microgravity states. It was reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…5b. Such a picture of composition rings has not only been provided by simulations, 10,11,24 but has also been verified in drop-tube experiments of Fe-Sn alloy. 11 At a temperature T 3 where the supersaturation reaches the critical value, the rings will break up into isolated globules, as displayed in Fig.…”
Section: Solidification Pathmentioning
confidence: 60%
See 2 more Smart Citations
“…5b. Such a picture of composition rings has not only been provided by simulations, 10,11,24 but has also been verified in drop-tube experiments of Fe-Sn alloy. 11 At a temperature T 3 where the supersaturation reaches the critical value, the rings will break up into isolated globules, as displayed in Fig.…”
Section: Solidification Pathmentioning
confidence: 60%
“…It was demonstrated by simulation that surface segregation before decomposition of the bulk liquid phase is favored thermodynamically. 10 Once a Bi-rich thin layer is formed on the surface, a coupled layer depleted in Bi emerges in its neighborhood, producing a concentration fluctuation along the radial direction of the droplet, as shown in Fig. 5b.…”
Section: Solidification Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…The extended Model H simulates the phase separation of the binary alloy [18] . In the light of the different systems, the phenomenological model introduced into the modified item describes the evolutionary characteristics of alloy melt.…”
Section: Phase Separation Modelmentioning
confidence: 99%
“…The phase-separation processes in Fe-Cu and Ni-Cu-Pb alloys have been simulated by field methods. It has been shown that the Cu-or Pb-rich phase always forms the outer layer because of surface segregation, whereas internal microstructural evolution is mainly controlled by Marangoni convection [14,15]. In contrast, much work remains to be done in understanding atomic-scale phase separation.…”
mentioning
confidence: 99%